Insecticidal efficacy of lichens and their metabolites - A mini review - M. B. Sachin, S. N. Mahalakshmi, T. R. Prashith Kekuda (Journal of Applied Pharmaceutical Science, 2018)
Interest in natural products possessing insecticidal activity is increased because of the drawbacks such as high cost, environmental pollution, effects on non-target organisms, and the emergence of resistant pests that are associated with the use of synthetic insecticides. Lichens are composite organisms comprised of a photobiont and a mycobiont. Lichens are used traditionally worldwide and many studies have shown the promising pharmacological properties of lichens, including insecticidal activity. The present review highlights the potential of lichen extracts and their metabolites as insecticidal agents. An extensive literature survey carried out revealed promising insecticidal properties of solvent extracts and metabolites of lichens against plant pests and insect vectors that transmit human diseases. Lichen metabolites such as usnic acid, atranorin, vulpinic acid, fumarprotocetraric acid, barbatic acid, norstictic acid, and diffractaic acid exhibit insecticidal activity. It appears from the literature survey that lichens and their metabolites can be employed as insecticidal agents to prevent and control insect pests that cause damages to plants and transmit diseases such as malaria, dengue, filariasis, and others.
Keywords: Lichens, lichen substances,insecticidal, larvicidal, usnicacid.